The effectiveness of a caries preventive program in mothers and infants - An 18- month follow-up study - Abidin Talha Mutluay; Merve Mutluay; Turksel Dulgergil (Elsevier, 2020)
Background/purpose: MS and LB, the primary bacteria groups responsible for dental caries, and high levels of these bacteria in the mother promote transmission from mother to infant. The aim of this study was prevention of maternal MS and LB transmission on infants by using different preventive strategies and inhibition of early childhood caries proggession. Materials and methods: This study was conducted with 50 mother-child pairs who were randomly allocated into either a study group or a control group (n = 25 each). Mothers in the study group were enrolled in a detailed preventive program that included elimination of dental caries with restorative and antibacterial procedures, whereas those in the control group received only a single episode of oral-health education. Results: After 18 months, significant MS and LB inhibition was observed in the study group (p < 0.0001). In addition, caries prevalence in the infants in the study and control groups was 0% and 20% respectively, and the difference between the two groups was statistically significant (p = 0.020). Conclusion: These results indicate that primary preventive intervention and oral-health instruction can significantly inhibit the MS and LB levels of mothers and prevent caries in their children during the early years of life.